2007
DOI: 10.1093/toxsci/kfm204
|View full text |Cite
|
Sign up to set email alerts
|

Quinoid Metabolites of 4-Monochlorobiphenyl Induce Gene Mutations in Cultured Chinese Hamster V79 Cells

Abstract: 4-Monochlorobiphenyl (PCB3) is a component of commercial polychlorinated biphenyl (PCB) products and is an airborne environmental pollutant. Our recent study with transgenic Fischer 344 rats revealed the mutagenic potential of PCB3 in the livers of male rats. PCB3 is converted in vitro to hydroxylated metabolites, to hydroquinones (HQs, e.g., 2',5'-HQ and 3',4'-HQ), and can be further oxidized to quinones (Qs, e.g., 2',5'-Q and 3',4'-Q). This raises the question whether the mutagenic potential of PCB3 is due t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 44 publications
1
42
0
Order By: Relevance
“…Although for a long time PCBs were thought to be strictly promoting carcinogens, a lower chlorinated congener (PCB3) was shown to induced point mutations in rat livers in vivo (Lehmann et al, 2007), and, in agreement with this, recent evidence suggests that particularly the lower-chlorinated congeners can be oxidized to genotoxic metabolites, such as arene oxides and quinone species (Espandiari et al, 2003, Espandiari et al, 2004, Robertson and Ludewig, 2011). In fact, the quinone metabolites of PCB3 increase gene mutations in vitro at low micromolar concentrations (Zettner et al, 2007), induce strand breaks (Xie et al, 2010), bind to and inhibit the nuclear protein topoisomerase II (Bender et al, 2006, Bender and Osheroff, 2007, Srinivasan et al, 2001, Srinivasan et al, 2002) and reduce telomerase activity resulting in shortened chromosomal telomeres in cells in culture (Jacobus et al, 2008). Interestingly, only the para -dihydroxy metabolite of PCB3 induced polyploidization and only the ortho -dihydroxy metabolite caused sister chromatid exchanges (Flor and Ludewig, 2010) indicating a binding to other, so far unidentified cellular proteins, as mediators of these genotoxic effects.…”
Section: Pcb Metabolite Associated Toxicitiesmentioning
confidence: 99%
“…Although for a long time PCBs were thought to be strictly promoting carcinogens, a lower chlorinated congener (PCB3) was shown to induced point mutations in rat livers in vivo (Lehmann et al, 2007), and, in agreement with this, recent evidence suggests that particularly the lower-chlorinated congeners can be oxidized to genotoxic metabolites, such as arene oxides and quinone species (Espandiari et al, 2003, Espandiari et al, 2004, Robertson and Ludewig, 2011). In fact, the quinone metabolites of PCB3 increase gene mutations in vitro at low micromolar concentrations (Zettner et al, 2007), induce strand breaks (Xie et al, 2010), bind to and inhibit the nuclear protein topoisomerase II (Bender et al, 2006, Bender and Osheroff, 2007, Srinivasan et al, 2001, Srinivasan et al, 2002) and reduce telomerase activity resulting in shortened chromosomal telomeres in cells in culture (Jacobus et al, 2008). Interestingly, only the para -dihydroxy metabolite of PCB3 induced polyploidization and only the ortho -dihydroxy metabolite caused sister chromatid exchanges (Flor and Ludewig, 2010) indicating a binding to other, so far unidentified cellular proteins, as mediators of these genotoxic effects.…”
Section: Pcb Metabolite Associated Toxicitiesmentioning
confidence: 99%
“…Semivolatile PCBs have triggered our research interest, as a number of studies have shown that lower chlorinated, so-called semivolatile PCBs are genotoxic (Oakley et al 1996a, b; Srinivasan et al 2001; Zettner et al 2007; Ludewig et al 2008). In our previous studies, we demonstrated that metabolites of 4-chlorobiphenyl (4-CB), the major congener determined in indoor air samples (Davis et al 2002), function as reducing co-substrates in prostaglandin H synthase (PGHS) metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Elevated concentrations of mono-and dihydroxylated metabolites of PCB-3 were shown to induce these types of lesions in vitro (Zettner et al, 2007;Flor & Ludewig, 2010).…”
Section: (D) Mutagenic Effectsmentioning
confidence: 95%
“…The mutagenicity of PCB-3, its mono-and dihydroxylated metabolites, and its 3′,4′-and 2′,5′-quinones was investigated in cultured Chinese hamster V79 cells (Zettner et al, 2007). Induction of gene mutations at the Hprt locus was determined by 6-thioguanine resistance.…”
Section: Pcb-1 Pcb-2 Pcb-3 and Metabolitesmentioning
confidence: 99%